2020
DOI: 10.1155/2020/3454783
|View full text |Cite
|
Sign up to set email alerts
|

e-Self-Assessment as a Strategy to Improve the Learning Process at University

Abstract: Background. Self-evaluation or autonomous evaluation, understood as a practice in which students can judge their own achievements and reflect on them, is considered a key element in the assessment process of college education. A common procedure at University environments is to apply information and communication techniques to carry out self-assessment activities and record answers. The aim is to analyse if the e-self-assessment improves student performance, using tests for objective and short answers as a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…Accordingly, self-assessment became more visible and deeper, helping to identify and narrow the gap between their knowledge acquisition and knowledge application, and consequently, address various misconceptions they had previously had in a traditional education environment and lead them toward active elements in the learning procedure (Azriel et al, 2005 ; Davydova, 2018 ; Groenendijk et al, 2020 ; Oyelere et al, 2018 ; Palaigeorgiou & Papadopoulou, 2019 ). Hence, self-assessment directs the students in their activities by playing the role of a meta-cognitive tool (Martínez et al, 2020 ). While creating a mentality that inspires learners to experience new things, this tool eliminates the fear of failure and gives them the power to get involved in fun learning experiences (Javid, 2014 ; Lee & Hammer, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, self-assessment became more visible and deeper, helping to identify and narrow the gap between their knowledge acquisition and knowledge application, and consequently, address various misconceptions they had previously had in a traditional education environment and lead them toward active elements in the learning procedure (Azriel et al, 2005 ; Davydova, 2018 ; Groenendijk et al, 2020 ; Oyelere et al, 2018 ; Palaigeorgiou & Papadopoulou, 2019 ). Hence, self-assessment directs the students in their activities by playing the role of a meta-cognitive tool (Martínez et al, 2020 ). While creating a mentality that inspires learners to experience new things, this tool eliminates the fear of failure and gives them the power to get involved in fun learning experiences (Javid, 2014 ; Lee & Hammer, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that SAQs assists students to take an active role in their learning process and promote self-directed learning. 16 Also, it serves as a revision tool to study for assessments. 17 As in 2019, students also asked for a reduction in the number of the activities and the addition of short explanatory videos before each unit (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…In detail, in higher education several studies have been identified (Leaf et al, 2009;Ibabe & Jauregizar, 2010;Wolffensperger & Patkin, 2013;Panadero & Romero, 2014;McKevitt, 2016;Li & Chen, 2016;Machera, 2017;Ndoye, 2017;Rivas & Arrufat, 2016;Sharma et al, 2016;Ozarslan & Ozan, 2016;Ndoye, 2017;Elgadal, 2017;Fraile, Panadero, & Pardo, 2017;Duque Micán & Cuesta Medina, 2017;Martínez, Mon, Álvarez, Fueyo, & Dobarro, 2020) that confirm the positive impact of self-assessment processes on learners' performance and learning.…”
Section: School Performancementioning
confidence: 91%
“…In addition, the collection of electronic portfolios promoted students' selfassessment practice and, thus, encouraged self-directed language learning. Also, in higher education, Martínez et al (2020) examined whether online self-assessment improves students' performance. Based on the main findings, online self-assessment improved students' performance and increased their level of satisfaction.…”
Section: Research In Sags and Sdlmentioning
confidence: 99%